2006
DOI: 10.3892/or.16.5.1021
|View full text |Cite
|
Sign up to set email alerts
|

Histological type of oncogenity and expression of cell cycle genes in tumor cells from human mesenchymal stem cells

Abstract: In previous experiments, a novel tumor cell line, which was characterized by dominated F6 mutated from human mesenchymal stem cells (hMSCs), was developed. The mechanism and biological characteristics of this mutation are still unclear. In this study, the histological type of F6 cells was investigated by immunohistochemistry with specific markers: vimentin, CD117, desmin, NSE and vWF. The characteristics of proliferation and metastasis were shown by PCNA (proliferating cell nuclear antigen), and nm23 and cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…p16, p21, and p53 have also been demonstrated to be significantly upregulated in senescent hBM-MSCs [39]. In comparison, at the late stage of the hBM-MSC lifespan, significantly increased expression was observed in p16 but not p21 nor p53 [40]. Therefore, p16 might be the key marker for hBM-MSC senescence.…”
Section: Discussionmentioning
confidence: 99%
“…p16, p21, and p53 have also been demonstrated to be significantly upregulated in senescent hBM-MSCs [39]. In comparison, at the late stage of the hBM-MSC lifespan, significantly increased expression was observed in p16 but not p21 nor p53 [40]. Therefore, p16 might be the key marker for hBM-MSC senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Bmi1‐deficient mice (Bmi1 −/− ) display defects in the hematopoietic, nervous, and skeletal systems . Previous studies showed that Bmi1 is expressed in bone marrow MSCs, and Bmi1 is used to immortalize bone marrow MSCs . We have previously showed that the bone formation defects in the Bmi1 −/− mice were not completely restored by Sirt1 overexpression.…”
Section: Introductionmentioning
confidence: 99%
“…Bmi-1 is required for the self-renewal and postnatal maintenance of hematopoietic stem cells (HSCs) (6,7) and neural stem cells from the central nervous system and peripheral nervous system. (8,9) Previous studies have reported that Bmi-1 also is expressed in bone marrow mesenchymal stem cells (BM-MSCs), (10) and Bmi-1 has been used to immortalize BM-MSCs. (11) It is unknown, however, whether defects in endogenous Bmi-1 can alter BM-MSCs.…”
Section: Introductionmentioning
confidence: 99%